(untitled) (Research, Society and Development, 2020)
The objective of the study was to evaluate AGA as a marker of inflammatory response in patients with tuberculosis (TB) during anti-TB treatment and its association with clinical and radiological parameters of the disease. Therefore, patients with TB (n=35) were evaluated, according to the time of anti-TB treatment: T1 (1 and 2 months of treatment) (n=16); T2 (3 and 4 months of treatment) (n=10); T3 (5 and 6 months of treatment) (n=11). To assess the potential of AGA as a marker, PCR was measured as a comparison parameter, measured by the turbidimetry technique. Clinical and radiological data were obtained from medical records. The AGA evaluation showed the average of values within the reference range. The T1 group showed significantly higher levels when compared to patients in the T2 group (p=0.006), with no difference in relation to the T3 group. There was also no difference between groups T2 and T3. The CRP levels at T1 were well above the reference value, a fact not observed in other times of anti-tuberculosis treatment (T2 and T3). There was a difference between T1 and T2 (p=0.01), with no other significant association demonstrated. A positive correlation was observed between CRP and AGA at T1 (ρ=0.8653), T2 (ρ=0.6691) and T3 (ρ=0.9282). There was no association between clinical and radiological parameters and AGA and CRP values. We conclude that AGA is a good marker for monitoring the prognosis of evolution according to the time of anti-tuberculosis treatment, and can be used in the routine of patients with TB.